NUMERICAL EXPERIMENTS FOR THE LASER MARKING BY OXIDATION, MELTING AND EVAPORATION OF AISI 304 STAINLESS STEEL SAMPLES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Theoretical numerical calculations and numerical experiments with the Temperaturfeld3D software were carried out for laser marking with a fiber laser of AISI 304 stainless steel samples. The theoretical numerical experiments are based on the interrelation of the quantities affecting the technological process, obtained from the heat conduction equation and the heat balance equation. Temperaturfeld3D is a specialized software for laser technological processes, which are characterized by small zones of influence. Temperature fields were obtained for different values of power density and speed. Graphs of the dependences of the critical power densities of melting and evaporation on the speed were constructed using both methods. Preliminary working intervals of the power density were determined for the studied speeds for laser marking by oxidation, melting and evaporation. The results obtained using both methods were compared and analysed in view of the capabilities and advantages of each of these methods.